Public awareness towards first aid management of epilepsy - M., Chaitra K.; Agrawal, Avinash; P., Varshini; H., Anil; Athani, Sweta (International Journal of Contemporary Pediatrics, 2019)
Background: Determination of attitude and awareness towards epilepsy in general population. Despite successfully achievement of management of epilepsy in hospitals, the efforts to assess the awareness and mass education is very limited. Methods: Total 880 participants were required to answer a series of questionnaires related to demographic data, awareness, attitude towards epilepsy with details of their first aid management and their source of information for the same. Results: Concerning attitude, 14.65% would object having their children associated with epilepsy. 72.16% would object to marry or their children marrying an epileptic. 8.86% thought epilepsy as a form of insanity. Concerning knowledge, the 33% will seek others help as a first aid measure and 50% don’t have any source of information regarding first aid management. Conclusions: The results indicate considerable amount of social stigma still exist and alarming fact was even the educated people still think it as a social stigma and are biased. Awareness needs to be enhanced through various knowledge campaigns. Stress on proper first aid measure to a seizing person needs to be addressed to remove fear and anxiety among the public.